Indicators of stress hematopoiesis in the blood predict COVID-19 progression in patients over 65 years old - Miodrag Vučić; Jelena Milenkovic; Boris Djindjic; Vladana Stojiljkovic; Dijana Stojanovic; Branka Djordjevic; Maja Milojkovic; Sanja Velickovic (Hematology)
Objectives Advanced age is a well-established risk factor for severe coronavirus disease 2019 (COVID-19). Exacerbated inflammation affects multiple organs, among which hematopoiesis responds by increased output of various cells. We aimed to determine the association between COVID-19 progression and large immature cell (LIC) counts, changes in erythrocyte and platelet distribution widths (RDW, PDW) with reference to patients’ age.Methods A total of 755 patients with complete blood cell (CBC) analysis in the first 24 h of hospitalization were enrolled. Patients were divided into two groups: under and above 65 years of age.Results The LIC counts were different in both groups (p < 0.003). However, only the senior patients had markedly different values of RDW and PDW (p < 0.001). The receiver operating characteristic (ROC) curve analysis provided increased LIC (AUC = 0.600), RDW (AUC = 0.609), PDW (AUC = 0.556), and platelet to LIC ratio (AUC = 0.634) as significant in discriminating outcome in the older group. Importantly, these results were not repeated in the younger patients. In the elderly, the progression was predicted with LIC cut-off at ≥ 0.305 × 109/L (OR = 3.166) and RDW over 12.15% (OR = 2.081).Discussion Aging is characterized by a decline in immunological competence with a compromised control of inflammation leading to a proinflammatory state. This background together with the actions of pathogens may lead to emergency myelopoiesis.Conclusion Our results point to the important differences between age groups regarding CBC-related parameters of stress hematopoiesis during severe infection. Higher LIC, RDW and PDW levels were reliable in the early identification of COVID-19 progression only in the elderly.